Essential Oil Analysis and Qualitative Chemical Detection of Secondary Metabolites of some Species of Salvia L., (Sage) Prevalent in Syria - بابوجيان, جورجيت; عيسى, نزار; صالح, عبير (Latakia University Journal -Biological Sciences Series, 2021)
This study included a study of the general chemical content of /4/ species of the genus Salvia in the Syrian Flora, in order: Salvia pinardii Boiss., Salvia judaica Boiss., Salvia sclarea L., and Salvia hierosolymitana Boiss. This is done by preparing organic extracts for the /4/ studied species in a cold soaking method, for two solvents: high-polarity ethanol and low- polarity chloroform. /15/ secondary metabolites that are naturally synthesized and formed in the plant have been detected among the extracts. The following secondary metabolites were found in all studied species with variations in their concentrations and compounds: flavonoids, tannins, alkaloids, glycosides, cardiac glycosides, turbines, bis and ternaids, and coumarins. We observed that S.pinardii was almost completely void of the alkaloids. The percentage of turbines, cardiac and deoxygenated glycosides were increased, and the genus S.hierosolymitana was characterized by the highest concentrations and persistence rates found in the majority of the secondary metabolites that were detected and in both ethanol and chloroform extracts. The essential oil was Extracted and also analyzed by Gas Chromatography/ Mass Spectrometry Analysis (GC-MS) technology, which revealed the presence of many active compounds common in the studied species of Salvia L. of flavones, flavonoids and flavonoids varying values, the highest value of 1,8-cineole (36.634) in S.pinardii, and the highest value of beta.-Caryophyllen (22.4969) was in S. judaica, the highest value of spathulenol (17.3024) was in S.sclarea, and the highest value for Germacrene-d (34.1949) in S.hierosolymitana.